Campaign communication and political marketing - Maarek, Philippe J. (Chichester Malden, MA Wiley-Blackwell, 2011)
"Campaign Communication and Political Marketing is a comprehensive, internationalist study of the modern political campaign. It indexes and explains their integral components, strategies, and tactics.. Offers comparative analyses of campaigns from country to country. Covers topics such as advertising strategy, demography, the effect of campaign finance regulation on funding, and more. Draws on a variety of intenational case studies including the campaigns of Barack Obama and Nicolas Sarkozy. Analyses the impact of digital media and 24/7 news cycle on campaign conduct."-- Provided by publisher.
Birth and rise of political marketing in the United States -- Political marketing: a global approach -- The means of analysis and information -- The traditional tools -- Audiovisual tools -- Direct marketing methods -- The growing importance of the Internet -- Structure and organization of the campaign -- The particularities of local campaigns -- Conclusion: how to use this book... -- Appendices. 1: Memorandum of understanding between the Bush and Kerry campaigns for the 2004 televised debates (extract) -- 2: Internet "final rules" decided by the Federal Elections Commission, March 27, 2006.
Includes bibliographical references and index.
Keywords: Political campaigns -- United States; Communication in politics -- United States; Marketing -- Political aspects; United States -- Politics and government